DISIPLIN KERJA KARYAWAN : PERAN MEDIASI KEPUASAN KERJA STUDI EMPIRIS DI UNIVERSITAS MUHAMMADIYAH SEMARANG, INDONESIA - Prapti Siswi Utami; Wyati Saddewisasi; Yuli Budiati (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Work discipline refers to employees' awareness and willingness to comply with all organizational regulations and applicable social norms. The phenomenon of inadequate work discipline among employees can be observed in their lack of adherence to work responsibilities and established policies. The interaction between the work environment, organizational culture, leadership style, and job satisfaction plays a crucial role in improving work discipline. This study aims to examine the influence of the work environment, organizational culture, and leadership style on the work discipline of employees at the Faculty of Nursing and Health Sciences (FIKKes), Muhammadiyah University of Semarang. This research adopts an explanatory approach with a quantitative methodology. The population of this study consists of all employees registered at FIKKes, Universitas Muhammadiyah Semarang (UNIMUS). The study uses a census sampling method, involving all 138 FIKKes UNIMUS employees. The analysis method employed in this research is SMART Partial Least Square (PLS). The test results indicate that the work environment, leadership style, and job satisfaction positively influence employee discipline. Additionally, the work environment positively impacts employee job satisfaction. Work discipline is also affected by the work environment through job satisfaction as a mediating factor. However, organizational culture has a negative impact on both discipline and job satisfaction. Moreover, leadership style does not influence job satisfaction. Neither leadership style nor organizational culture affects work discipline through job satisfaction as a mediating variable.